Bibliometric trend analysis in a decade of European Orthopaedic literature - Mani, Olimpia; Nucci, Anna Maria; Scaglione, Michelangelo; Bonicoli, Enrico; Parchi, Paolo Domenico; Piolanti, Nicola (Acta Biomedica Atenei Parmensis, 2021)
Purpose The purpose of this bibliometric study was to summarize European orthopedic literature produced by EFORT memberships between 2009 and 2019 and to identify the 100 most cited articles, analyzing the characteristics that made them so interesting for the orthopedic scientific world. Method A search of the literature was conducted using Clarivate Analytics Web of Science in the subject category “orthopaedics”; then the results were summarized using Web of Science tools. Results A total of 160.375 articles were found: most of these were produced by England. In particular the most prolific institution was the University of London. Analyzing in detail the 100 most cited publications emerged that most of them were review published in journal with high impact factor (Q1). The University of Oxford was the institution with the greatest number of contributions (13%). The most cited topics were osteoarthritis (24%), followed by orthopedic basic science (22%). Biomaterials was the most common topic by ordering the 100 analyzed articles according to “usage count”, a recent indicator of the level of interest in a specific item. Conclusion This bibliometric study can be useful to identify topics of interest for future scientific research and to outline the features that make some publications more interesting than others.